An Iridium Complex as an AIE‐active Photosensitizer for Image‐guided Photodynamic Therapy. Issue 13 (26th May 2021) - Yang, Ke; Zhou, Yi; Wang, Yaping; Zhao, Shaojing; Wu, Xiaoli; Peng, Xiao; Huang, Li; Jiang, Lirong; Lan, Minhuan; Yi, Xiao‐Yi
Abstract: Image‐guided photodynamic therapy (PDT) has received growing attention due to its non‐invasiveness and precise controllability. However, the PDT efficiency of most photosensitizers are decreased in living system due to the aggregation‐caused singlet oxygen ( 1 O2 ) generation decreasing. Herein, we present an Iridium (III) pyridylpyrrole complex (Ir‐1) featuring of aggregation‐induced emission (AIE) and 1 O2 generation characteristics for image‐guided PDT of cancer. Ir‐1 aqueous solution exhibits bright red phosphorescence peaked at 630 nm, large Stokes shift of 227 nm, and good 1 O2 generation ability. The 1 O2 generating rate of Ir‐1 in EtOH/water mixture solution is 2.3 times higher than that of Rose Bengal. In vitro experimental results revealed that Ir‐1 has better biocompatibility and higher phototoxicity compared with clinically used photosensitizers (Rose Bengal and Ce6), suggesting that Ir‐1 can serve as a photosensitizer for image‐guided PDT of cancer. Abstract : An Iridium (III) complex (Ir‐1) featuring aggregation‐induced emission and 1 O2 generation characteristics were prepared. Ir‐1 has better biocompatibility and higher phototoxicity compared with clinically used photosensitizers. The application of Ir‐1 in imaging‐guided photodynamic therapy was demonstrated.